The Influence of The Socialization of "Ojek Sigap: Ojek Siap Gerak Cepat (Quick Response Motorcycle Taxi: Ready To Move Fast) on Knowledge of First Aid For Accidents of Online Ojek Drivers in Jambi City - Andi Subandi; Dwi Noerjoedianto; Elsa Volinda Sari (The International Science of Health Journal, 2025)
Road traffic accidents are the leading cause of death worldwide, with the current global death toll reaching 1.24 million per year. This figure is expected to increase to 3.6 million per year by 2030. Indonesia ranks third highest in Asia, after China and India, with 38,279 deaths due to road traffic accidents in 2015. Jambi City, despite having a lower accident rate than other provinces, still faces significant challenges with 392 deaths in 2018. Lack of knowledge about first aid (P3K) is one of the factors contributing to the high death toll. Given the widespread use of online motorcycle taxis on the road, their drivers have the potential to become witnesses or victims of accidents. Therefore, it is necessary to improve knowledge and skills in first aid among online motorcycle taxi drivers to improve road safety. The study used the Pre - Experimental research method with a Prepost Test Design design with 28 respondents. The provision of material using educational videos and mnemonic cards related to initial handling of accidents. Statistical analysis using the Wilcoxon test showed very significant results with a value of P = 0.0000 and Z = -4.658. A very low P value (less than 0.05) indicates that there is a statistically significant difference between the level of knowledge of respondents before and after the socialization. This negative Z value indicates that there is a significant increase in the knowledge of respondents after they have participated in the socialization program. The results of the study indicate that there is an Influence of the Socialization of "OJEK SIGAP” on Knowledge of First Aid for Accidents for Online Ojek Drivers in Jambi City.